2007
DOI: 10.1007/s10646-007-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in diet and livers of Black-crowned Night Heron Nycticorax nycticorax and Grey Heron Ardea cinerea chicks from Pyeongtaek, Korea

Abstract: This study presents concentrations of iron, manganese, zinc, copper, lead and cadmium in diet and livers of Black-crowned Night Heron Nycticorax nycticorax and Grey Heron Ardea cinerea chicks from Pyeongtaek, Gyeonggi-do, Korea. Heavy metal concentrations of heron chicks were not related to concentrations in the diet. Copper concentrations were significantly greater in the diet of Black-crowned Night Herons (geometric mean = 13.6 wet microg/g) than Grey Herons (7.45 wet microg/g), other metal concentrations di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 29 publications
(49 reference statements)
0
22
0
2
Order By: Relevance
“…The tail feathers may also reflect the body burden of lead and cadmium (Dauwe et al 2002). High external contamination of tail feathers is probably related to lead-contaminated soil particles and the dust that is absorbed on plumage when the birds forage on the contaminated soils (Weyers et al 1988;Kim and Koo 2007a). Dauwe et al (2002) suggested that Pb concentrations in tail feathers could be due to either internal deposition via blood in growing feathers or to an external contamination due to excretion of the uropygial gland (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The tail feathers may also reflect the body burden of lead and cadmium (Dauwe et al 2002). High external contamination of tail feathers is probably related to lead-contaminated soil particles and the dust that is absorbed on plumage when the birds forage on the contaminated soils (Weyers et al 1988;Kim and Koo 2007a). Dauwe et al (2002) suggested that Pb concentrations in tail feathers could be due to either internal deposition via blood in growing feathers or to an external contamination due to excretion of the uropygial gland (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Koo (2007b) reported that cadmium contents in feathers of wild birds increased in relation to cadmium concentrations in the diet. Greater concentrations of Cd in herons and egrets have also been associated to contamination in their feeding grounds (Kim and Koo 2007a). Higher Cd concentration in feathers and sediments indicates its wide distribution in the environment which consequently deposited into feathers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These species can provide interesting data to monitor the quality of the environment (Kim and Koo 2008). Many studies have recommended herons and egrets as bioindicators for heavy metals in aquatic systems and local pollution around breeding sites (Kim and Koo 2007;Boncompagni et al 2003). Because herons and gulls are at the top of their trophic level and can yield information over a large area around each sampling site, they provide information not only on bioavailability of contaminants but also on how, where, and when they are transferred within the food web (Battaglia et al 2005).…”
mentioning
confidence: 99%